You can use substitution here. First, get y alone:
14x + y = -4
subtract 14x from each side
y = -4 - 14x
Then, plug y into the second equation
-4 - 14x = 3x² - 11x - 4
then solve from there
Hope this helps :)
Answer:
30
Step-by-step explanation:
60=whole
60/2=30
Answer:
(x - 2)(5x + 3) = 0
Step-by-step explanation:
5x² - 7x - 6 = 0
Consider the factors of the product of the x² term and the constant term which sum to give the coefficient of the x- term.
product = 5 × - 6 = - 30 and sum = - 7
The factors are - 10 and + 3
Use these factors to split the x- term
5x² - 10x + 3x - 6 = 0 ( factor the first/second and third/fourth terms )
5x(x - 2) + 3(x - 2) = 0 ← factor out (x - 2) from each term
(x - 2)(5x - 3) = 0 ← in factored form
Answer:
A(r)=15-3r
Step-by-step explanation:
switch the sign of +3r to make it -3r